Educating for Professional Life : Twenty-five Years of the University of Westminster - Penn, Elaine (London University of Westminster Press, 2017)
"The story of the University of Westminster is the fifth volume in a series of titles exploring the University's long and diverse history. This book celebrates the twenty-fifth anniversary of the institution gaining university status, the right to award its own degrees and to participate in publicly funded research. Drawing on extensive research conducted in the University of Westminster Archive this volume investigates the evolution from Polytechnic to University within the broader context of the transformation of UK higher education in the late twentieth and early twenty-first centuries. A print paperback can be purchased direct from the University of Westminster for £20 by following this link: http://www.westminster.ac.uk/historybooks. Staff, students and alumni can claim a 20% discount on this price."
University of Westminster
English
Keywords: Institutions & learned societies: general; Social & cultural history; History of education; Educational strategies & policy; Higher & further education, tertiary education; Universities; Polytechnic movement; Polytechnic of Central London; PCL; higher education; University of Westminster